An Estimated Labor and Financial Friction Model: Evidence from the Korean Economy - 김태봉 (계량경제학보, 2022)
This study uses a DSGE model with a financial accelerator mechanism and involuntary unemployment to analyze the Korean economy. First, the fully specified model outperforms the New Keynesian model in terms of implied volatilities. Second, the structural shocks in the financial friction model have more amplification effects on macroeconomic variables than those in the New Keynesian model. Third, the “Fisher deflationary effect” is not significant. Fourth, the contributions of domestic shocks are more pronounced than those of foreign shocks. Fifth, the financial risk shock has a significant effect on investment. Sixth, the global financial crisis was driven by aggregate demand shocks, aggregate supply shocks, and foreign shocks. However, the pandemic crisis was mostly driven by adverse aggregate supply shocks, while the adverse foreign shocks’ contributions were short-lived. Seventh, policy shocks played important roles in dampening the adverse effects of shocks, especially on output and unemployment rates.
Keywords: DSGE model; financial accelerator; involuntary unemployment